What does Caravaggio have to do with "muzz" influx into Europe? Controversial street murals in Brussels and the question of political street art. Issue 1 (31st December 2022) - Ayaydin, Deniz Berfin
ABSTRACT: Brussels has been the scene for a number of murals depicting sexually explicit and violent acts since 2016. Both online and offline discussions surrounding the murals reveal the complexities between visibility regimes and public spaces. While street art literature has grown in various academic areas, street art remains undertheorised, especially when it comes to public reactions. How street art becomes politicised in relation to socio-political realities also remains to be examined. By analysing online discussions about murals in Brussels depicting violence and sexually explicit imagery, this article aims to contribute to the scholarship on the relationship between street art and politics. I try to categorize what is seen as political in street art by scholars as political praxis and political impact . I argue that when political praxis 's invitation to engage with the object and reflect on its particular socio-political context is taken up by spectators, the street art generates political meanings that can tie Caravaggio to ISIS.This formulation of the political does not rest in the art object, the artist's intention or the public's reception, but in the potential for the realisation of human relations around the artwork.